2019
DOI: 10.1109/access.2019.2958645
|View full text |Cite
|
Sign up to set email alerts
|

Topology Optimization With Selective Problem Setups

Abstract: Topology optimization has demonstrated its power in structural design under a variety of physical disciplines. Generally, a topology optimization problem is formulated with clearly-defined problem setup. Both design domain shape and boundary condition are clearly-defined during pre-processing. Optimization with multiple choices of design domains or boundary conditions have to be performed with multiple runs of the algorithm to make the best choice among the selective problem setups. The computational cost is p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…For example, this approach has been applied to the optimization of the rotor geometry of a PMSM through utilizing a genetic algorithm in [26], and a combination of rotor core TO with identification of current phase angle was described in [27]. TO is not limited to electrical machine design but can be implemented for a huge variety of technical problems [22].…”
Section: Topology Optimizationmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, this approach has been applied to the optimization of the rotor geometry of a PMSM through utilizing a genetic algorithm in [26], and a combination of rotor core TO with identification of current phase angle was described in [27]. TO is not limited to electrical machine design but can be implemented for a huge variety of technical problems [22].…”
Section: Topology Optimizationmentioning
confidence: 99%
“…Nonetheless, the majority of previous works has dealt with LSPMSMs using the same predefined geometry for optimization based on the squirrel-cage bars adopted from classic IMs. Furthermore, no activities are reported that deal with topology optimization (TO) [22] for LSPMSM performance improvement. This is in contrast to PMSMs, where many such studies can be found, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…This is only partly reflected in current optimization approaches. These target specific FLM optimization problems (Brackett, Ashcroft & Hague 2011;Liu et al 2018;Fu et al 2019). Dapogny et al (2019) derived geometry which is dependent on chosen infill raster.…”
Section: Introductionmentioning
confidence: 99%